Natural Ventilation Performance of Kedah Vernacular House - Abd. Wahab, Izudinshah; Hakim Ismail, Lokman (International Journal of Sustainable Construction Engineering and Technology, 2014)
As processed energy becoming more expensive, people have started to look for natural sources for option to provide their needs and comfort. Natural ventilation is one of the passive approaches that have recently become one of the important approaches in building design. However, architecturally, this approach is not considered new as a lot of previous buildings before industry era are totally depending on natural sources to ventilate their indoor spaces. Therefore this study was done to look into how these architectural details in Malay vernacular houses may affect the air movement performance around them. Two case studies of vernacular houses were chosen with design elements identified as natural ventilation attributes. Several points were identified inside and outside of the house where the wind speed of their surrounding were taken hourly in daytime for three days. The data were than compared to the building elements of the spaces. Both houses shows how building orientation and position of ventilation openings play the major role in determine the indoor air movement performance. However due to having other unintentionally openings such as gaps on roof design and gaps in flooring construction installation may also allow air flow to sip into the building despite of not having proper opening facing the cross ventilation. Besides that, by having openings at high level at the high roof may also encourage natural air flow via stack effect ventilation. Wide and full height window design may also become one of the most significant element to allow ventilation as proven in this research.